Business and Economy: Recent Updates 2020
DOI: 10.37247/beru.1.2020.7
|View full text |Cite
|
Sign up to set email alerts
|

Capital budgeting practices by non-financial companies listed on Kuwait Stock Exchange (KSE)

Abstract: The purpose of this study is to investigate various aspects of capital budgeting techniques adopted by Kuwaiti nonfinancial companies listed on the Kuwait Stock Exchange (KSE).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…In a more recent study, Gupta and Batra (2016) reported an association between the techniques used and firm size in India. In Kuwait, Al- Mutairi et al (2018) found the nature of the project under assessment and the academic and professional capabilities of corporate personnel as the determinant for the choice of techniques. Within the context of developed countries, Daunfeldt & Hartwig (2014) discovered that the choice of capital budgeting techniques of firms listed on the Stockholm Stock Exchange depended very much on leverage, growth opportunities, dividend payout ratios, choice of targeted debt ratio, industry and CEO personal traits.…”
Section: Prior Studies On Capital Budgetingmentioning
confidence: 99%
See 1 more Smart Citation
“…In a more recent study, Gupta and Batra (2016) reported an association between the techniques used and firm size in India. In Kuwait, Al- Mutairi et al (2018) found the nature of the project under assessment and the academic and professional capabilities of corporate personnel as the determinant for the choice of techniques. Within the context of developed countries, Daunfeldt & Hartwig (2014) discovered that the choice of capital budgeting techniques of firms listed on the Stockholm Stock Exchange depended very much on leverage, growth opportunities, dividend payout ratios, choice of targeted debt ratio, industry and CEO personal traits.…”
Section: Prior Studies On Capital Budgetingmentioning
confidence: 99%
“…Capital budgeting is a major terrain in the sphere of financial management. It is defined as a set of procedures, routines, methods and techniques used for making decisions on how to allocate resources among investment projects so that corporate profitability and the financial growth of a firm is ensured (Segelod, 1998;Al-Mutairi, Naser, & Saeid, 2018). This is supported by the International Federations of Accountants (2013) which stated that to maintain a strong and sustainable economic growth, it is important for a firm to adopt a systematic, analytical and thorough investment appraisal approach that is sound in judgement.…”
Section: Introductionmentioning
confidence: 99%
“…This paper uses a survey approach to investigate how managers make their investment decisions in practice in line with papers from authorities such as Arnold and Hatzopoulos (2000), Graham andHarvey (2001), Du Toit andPienaar (2005), Correia and Cramer (2008), Maroyi and van der Poll (2012), Maquieira et al (2012), Batra and Verma (2017) and Al-Mutairi et al (2018). Survey studies are rare in finance, but the nature of survey data offers a unique perspective that supports bridging the gap between theory and practice.…”
Section: Introductionmentioning
confidence: 99%
“…results also indicate the continual use of PBK due to the simplicity of the technique.On a scale of 1-5,Schlegel et al (2016), using data from 65 German manufacturing companies, find a median usage pattern of NPV (5.0), PBK (3.5) and IRR (3.0). In Kuwaiti,Al-Mutairi et al (2018), using data from non-financial companies listed on the Kuwait Stock Exchange (KSE), find a usage pattern of NPV (1st rank), PI (2nd rank) and IRR (3rd rank). They further state that the nature of the project under assessment and corporate staff's academic/professional capabilities determine the techniques used.…”
mentioning
confidence: 99%
“…The selection of a particular capital investment is based on the most efficient use of funds in anticipation of expected flow of benefit over a period of time. Capital budgeting decision according to Al-Mutairi et al, (2018) [7] is seen as important decision in corporate finance because it creates accountability and measurability. Accountability in the sense that its owners or shareholders would see any firm seeking to make a capital investment without evaluating the risks and potential rewards as beingirresponsible.…”
Section: Introductionmentioning
confidence: 99%